Technological features of combining condensed canned milk with sugar and fruit-berry syrups during processing - Ryabokon, Natalia; Rindyuk, Dmitry; Shpak, Maksim; Komisar, Ksenia (My University, 2014)
A mathematical model of combining milk and plant products was built on the basis of dependency of mass fraction of solids condensed canned milk (CCM).with sugar and FBS of mass fraction of solids milk-sugar mixture and the temperature of intensified lactose crystallization. Taking into consideration the rheological characteristics and constructive-technological parameters, the degree of homogeneity consistency and duration of formation of condensed milk with sugar and fruitberry syrup "cranberry-blueberry" were studied.
Keywords: згущені молочні консерви з цукром; сгущенные молочные консервы с сахаром; condensed canned milk with sugar; молочно-цукрова основа; молочно-сахарная основа; milk-sugar base; плодово-ягідний сироп; плодово-ягодный сироп; fruit - berry syrup; математична модель; математическая модель; mathematical model; однорідність; однородность; homogeneity; тривалість; продолжительность; duration; кафедра машин і апаратів харчових та фармацевтичних виробництв; кафедра теоретичної механіки та ресурсоощадних технологій